Virtual networks: Why do students use Instagram? - Kaperonis, Stavros (Homo Virtualis, 2019)
Instagram has become the bridge between consumers who share moments from their lives and companies that share their products and services with the users. Instagram stands out from the other social media networks thanks to user-friendly toolkit that provides photo editing, video sharing and Instagram stories. This conceptual model research investigates the impact of Instagram on user's attitude. Data were collected from young Instagram users in order to measure if there is a relationship between specific factors of Instagram and user attitude through Structural Equation Modeling (SEM). In this research, will be analyzed the consumer behavior in social media and particularly on Instagram. As a first stage of our research we are going to develop the theoretical study for Instagram users (n=200) at the age of 18-34, investigating the behavior of use Instagram which is determined by social presence. This study presents a theoretical conceptual model based on the theory of social presence, perceived pleasure, perceived usefulness and perceived value on Instagram and the potential connection of those factors to the user attitude.